2019
DOI: 10.1101/677054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Depletion of Ric-8B leads to reduced mTORC2 activity

Abstract: AbstractmTOR, a serine/threonine protein kinase that is involved in a series of critical cellular processes, can be found in two functionally distinct complexes, mTORC1 and mTORC2. In contrast to mTORC1, little is known about the mechanisms that regulate mTORC2. Here we show that mTORC2 activity is reduced in mice with a hypomorphic mutation of the Ric-8B gene. Ric-8B is a highly conserved protein that acts as a non-canonical guanine nucleotide exchange factor (GEF) for heterot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…As Ctu2, a tRNA-modifying enzyme acting in the same cascade as Elp3, also promotes mTORC2 activation, it is likely that these enzymes are required for the translation of mRNA candidates acting as activators of mTORC2. In this context, we identified Ric8b, a candidate known to promote mTORC2 activation (Nagai et al, 2020), as a direct target of Elp3. Ric8b expression is induced by IL-4 in macrophages, similarly to Elp3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Ctu2, a tRNA-modifying enzyme acting in the same cascade as Elp3, also promotes mTORC2 activation, it is likely that these enzymes are required for the translation of mRNA candidates acting as activators of mTORC2. In this context, we identified Ric8b, a candidate known to promote mTORC2 activation (Nagai et al, 2020), as a direct target of Elp3. Ric8b expression is induced by IL-4 in macrophages, similarly to Elp3.…”
Section: Discussionmentioning
confidence: 99%
“…As Elp3 and mTORC2 deficiencies share overlapping phenotypes (Hallowell et al, 2017), we next looked for any positive regulator of mTORC2 activation whose translation may require Elp3. In this context, we got interested in Ric8b, a noncanonical guanine nucleotide exchange factor (GEF) whose deficiency impairs Akt phosphorylation on Serine 473 (Nagai et al, 2020)…”
Section: Elp3 Promotes Ric8b Expression In Myeloid Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the human data, we also found that Gα13 loss in the KPC mouse model enhanced mTOR signaling. Notably, GPCRs and G proteins have been shown to modulate mTOR signaling (Gan et al, 2019; Jewell et al, 2019; Nagai et al, 2020; Puertollano, 2019). For example, Gαs-coupled GPCRs activate protein kinase A to inhibit mTOR complex 1 in multiple cell lines and mouse tissue (Jewell et al, 2019).…”
Section: Discussionmentioning
confidence: 99%